Homœopathic remedies used in the clinical syndrome of habitual hyperventilation - Davies, Anita E. (British Homeopathic Journal, 1980)
An acute hypocapnoeic attack is described which was precipitated by extreme physical hard work in an obese subject who had recently been bereaved. The symptoms of anxiety and depression are repertorized. Twenty-five out of the 64 remedies shown were used in a personal series of patients which formed the basis of the present study. Arsenicum album and Sepia are the most commonly used “chilly” remedies, and Lycopodium, Phosphorus and Pulsatilla were frequently indicated.The symptoms of chronic hypocapnoea are reviewed. The homœopathic approach to a patient suffering from this disorder is discussed, and the chief symptoms are repertorized, starting from the rubric “Anxiety” in Kent's Repertory.Hering's Laws of Cure, from within out, from above down, and from more important to less important organs, are illustrated by reference to three case histories. The final case is then briefly reviewed with the pathological findings and Dr C. O. Kennedy discusses the prescribing symptoms.